Бінарність базових вербалізаторів концепту Дорога/Road/Weg в українській, російській, англійській та німецькій мовах - Бондар, Тетяна Георгіївна; Bondar, T. H. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті показано, що однією з характерних ознак маніфестації концепту ДОРОГА/ROAD/WEG в україн¬ській, російській, англійській та німецькій мовах є наявність не одного, а двох основних лексем-вербалізаторів. Дані тлумачних словників засвідчують, що лексикографи відчувають повну тотожність базової семантики українських лексем дорога та шлях, російських лексем дорога та путь, англійських road і way, німецьких Weg і Bahn. Цей факт слугує доказом бінарності базових вербалізаторів концепту ДОРОГА/ROAD/WEG. The article deals with typological similarity of main verbalizers of the concept ДОРОГА/ROAD/WEG in the Ukrainian, Russian, English and German languages. The author draws attention to the fact that there are two basic lexemes for the concept representation in each of the four languages. They are дорога – шлях in Ukrainian, дорога – путь in Russian, road – way in English and Weg – Bahn in German. These lexemes can be looked upon as semantic equivalents. Lexicographers (authors and editors of explanatory dictionaries) feel a complete semantic identity of binary lexemes. This fact proves binarity of the basic language representatives of the concept ДОРОГА/ROAD/WEG in two Slavic and two Germanic languages.
Binarity of Basic Verbalizers of the Concept Дорога/Road/Weg in the Ukrainian, Russian, English and German Languages
Keywords: концепт; concept; вербалізатор; verbalizer; бінарність; binary